Seroprevalence and Co-infection of Hepatitis A and Hepatitis E Viruses in Children – A Hospital Based Study in Bangladesh - Naher, Bodhrun; Ahmed, Khondaker Mobasher; Islam, Md Rafiqul; Mazumder, Md Wahiduzzaman; Rukunuzzaman, Md Rukunuzzaman (Journal of Comilla Medical College Teachers' Association, 2024)
Background: Viral hepatitis is a serious health problem globally and in endemic countries like Bangladesh. Viral hepatitis may present as mono-infection or co-infection caused by hepatitis A virus (HAV), hepatitis B virus, hepatitis C virus, hepatitis D virus, and hepatitis E virus (HEV). Enterically transmitted viral agents like Hepatitis A virus (HAV) and Hepatitis E virus (HEV) are common causes of viral hepatitis in developing countries. As the routes of entry are similar double infections by both agents are common. Co-infection with two or more viruses may lead to serious complications and increased mortality. Objective: This study was carried out to learn about the seroprevalence of HAV & HEV (and double infections if any) infections in acute viral hepatitis (AVH) cases attending our hospital. Methods: This is a retrospective cross-sectional study of a 2 years duration carried out in the Pediatric Gastroenterology and Nutrition department of BSMMU, Dhaka. Total 400 cases, presenting with Acute Viral Hepatitis were included in the study. Cases with suggestive history were tested for IgM anti-HAV and IgM anti-HEV respectively. Results: Out of 400 samples, 100 samples were positive for HAV and/or HEV infection with an overall prevalence of 24.7%. HAV & HEV seroprevalence in AVH cases were found to be 13.75% (55/400) and 5.75% (23/400), respectively. Dual infection of HAV and HEV was found in 5.25% (21/400) of study subjects. Both year, most of the positive cases are seen in the months of August and September. Conclusion: Seroprevalence of HAV was 13.75%, HEV 5.75% and dual infection of HAV & HEV 5.25% in the current study. J Com Med Col Teachers’ Asso July 2023; 27(2): 52-56